2015
DOI: 10.3762/bjoc.11.129
|View full text |Cite
|
Sign up to set email alerts
|

Thiazole-induced rigidification in substituted dithieno-tetrathiafulvalene: the effect of planarisation on charge transport properties

Abstract: SummaryTwo novel tetrathiafulvalene (TTF) containing compounds 1 and 2 have been synthesised via a four-fold Stille coupling between a tetrabromo-dithienoTTF 5 and stannylated thiophene 6 or thiazole 4. The optical and electrochemical properties of compounds 1 and 2 have been measured by UV–vis spectroscopy and cyclic voltammetry and the results compared with density functional theory (DFT) calculations to confirm the observed properties. Organic field effect transistor (OFET) devices fabricated from 1 and 2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In the case of attractive interactions the electronic structure of the compound might be affected not only by an improvement of the conjugation upon planarisation, but by the direct influence of the heteroatom on the electroactive unit it is interacting with in the planar molecular conformation. In a recent paper, 24 we have shown that substitution of peripheral thiophene units by more electron deficient thiazole moieties in an H-shaped hybrid TTF-terthiophene compound (20 and 21, respectively), in fact destabilises the HOMO, which is located on the central TTF unit. Such direct control over frontier orbital energy levels through non-covalent interactions opens up a new strategy of tailoring the electronic structure of organic semiconductors.…”
mentioning
confidence: 93%
“…In the case of attractive interactions the electronic structure of the compound might be affected not only by an improvement of the conjugation upon planarisation, but by the direct influence of the heteroatom on the electroactive unit it is interacting with in the planar molecular conformation. In a recent paper, 24 we have shown that substitution of peripheral thiophene units by more electron deficient thiazole moieties in an H-shaped hybrid TTF-terthiophene compound (20 and 21, respectively), in fact destabilises the HOMO, which is located on the central TTF unit. Such direct control over frontier orbital energy levels through non-covalent interactions opens up a new strategy of tailoring the electronic structure of organic semiconductors.…”
mentioning
confidence: 93%
“…In the past two decades, many polycyclic aromatic compounds have been developed as high-performance OSC materials. [12] In addition, the results of several studies show that the performance of these materials is controlled by solid state molecular orientation governed by intermolecular interactions, exemplified by p•••p interaction, [12] CH•••p interaction, [13] S•••S contact, [14] and S•••N contact [15] to construct brickwork, [16] herringbone, [1], [17] [18][19] [20] [21] and slipped-p-stacked crystal structure. [22] Actually, some linearly-fused p-electronic systems exhibit high charge-carrier mobilities as a result of their closepacked crystalline structures.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 TTF-based materials have been developed for potential use within various applications including organic photovoltaic cells, 11,12 cation sensors 13,14 and organic field effect transistors. [15][16][17] Increasing the conjugation in TTF-based systems contributes to forming an increasingly polarisable species which is more likely to be involved in intermolecular interactions. Increasing the conjugation is also utilised in the stabilisation of the radical cation and dication which facilitates charge transport in the material.…”
Section: Introductionmentioning
confidence: 99%